Salinity and prey concentration on larviculture of killifish Hypsolebias radiseriatus (Cyprinodontiformes: Rivulidae) - Araújo, Luciano Medeiros de; Gonçalves Junior, Lucas Pedro; Silva, Walisson de Souza e; Luz, Ronald Kennedy (Acta Scientiarum. Animal Sciences, 2020)
The aim of this study was to investigate the tolerance of Hypsolebias radiseriatus larvae to different salinities, and the effects of different prey concentrations and water salinities on the larviculture of this species. Salinity tolerance was tested by subjecting newly-hatched larvae to 96 hours of osmotic shock testing (experiment I) and gradual acclimatization (experiment II) of the following salinities: freshwater (control), 2, 4, 6 and 8 g of salt L-1. A third experiment (experiment III) evaluated three water salinities (S0 - freshwater, S2 - 2 g of salt L-1 and S4 – 4 g of salt L-1) and three initial daily prey concentrations (100, 300 and 500 artemia nauplii larva-1). In experiments I and II, survival was only influenced by the salinity of 8 g of salt L-1 (p < 0.01). After 35 days, weight was only influenced by prey concentration (p < 0.05), with the highest value being with 500 artemia nauplii larva-1. The lowest survival was for 4 g of salt L-1 and for 100 artemia nauplii larva-1. H. radiseriatus larviculture can be carried out in salinity of up to 2 g of salt L-1 and initial daily prey concentrations with 500 artemia nauplii larva-1.